A REAPPRAISAL OF GENERIC AND SUBGENERIC CLASSIFICATION IN THE BATRACHOSPERMACEAE (RHODOPHYTA) - Necchi, O.; Entwisle, T. J. (Int Phycological Soc, 1990)
The generic and subgeneric classification of the family Batrachospermaceae (Rhodophyta) has long been recognized as ambiguous and often inconsistent. One of the prime features used to delineate sections of Batrachospermum, trichogyne shape, is variable even within given species. However, characters associated with the carposporophyte and the carpogonial branch, as well as carpogonial symmetry, are practical and consistent taxonomic criteria. These features have been used to redefine sectional delineation in Batrachospermum. Based on phylogenetic reasoning and practicality, it is proposed that the three genera Nothocladus, Sirodotia and Tuomeya be reduced to sectional level within Batrachospermum. The genus Batrachospermum would thus become the sole member of the Batrachospermaceae and would include two subgenera, Batrachospermum and Acarposporophytum, the former with nine clearly defined sections (Aristata, Batrachospermum, Contorta, Hybrida, Nothocladus (Skuja) stat. nov., Sirodotia (Kylin) stat. nov., Tuomeya (Harvey) stat. nov., Turficola and Viridia). As a result, the following nomenclatural changes are proposed: Batrachospermum lindaueri (Skuja) comb. nov., B. nodosum (Skuja) comb. nov., B. delicatulum (Skuja) comb. nov., B. fennicum (Skuja) comb. nov., B. suecicum (Kylin) comb. nov. and B. americanum (Kutzing) comb. nov.